2021
DOI: 10.1016/j.cocis.2021.101479
|View full text |Cite
|
Sign up to set email alerts
|

Surfactants – Compounds for inactivation of SARS-CoV-2 and other enveloped viruses

Abstract: We provide here a general view on the interactions of surfactants with viruses, with a particular emphasis on how such interactions can be controlled and employed, for inhibiting the infectivity of enveloped viruses, including coronaviruses. The aim is to provide to interested scientists from different fields, including chemistry, physics, biochemistry, and medicine, an overview over the basic properties of surfactants and (corona)viruses, which are relevant to understanding the interactions between the two. V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 169 publications
(200 reference statements)
0
50
0
Order By: Relevance
“…Soaps or detergents (which by definition are surfactants-see below) begin to destabilize the lipid component of the envelope, leading to fragmentation of the lipid bilayer with embedded proteins. There is association of these fragments with surfactant monomers and possible micellization of these fragments, as well as of free proteins (Le Maire, Champeil & Møller, 2000;Simon et al, 2021), as depicted in Fig. 4.…”
Section: Handwashing With Soap and Water Leads To Inactivation And Removal Of Pathogensmentioning
confidence: 98%
See 2 more Smart Citations
“…Soaps or detergents (which by definition are surfactants-see below) begin to destabilize the lipid component of the envelope, leading to fragmentation of the lipid bilayer with embedded proteins. There is association of these fragments with surfactant monomers and possible micellization of these fragments, as well as of free proteins (Le Maire, Champeil & Møller, 2000;Simon et al, 2021), as depicted in Fig. 4.…”
Section: Handwashing With Soap and Water Leads To Inactivation And Removal Of Pathogensmentioning
confidence: 98%
“…While it might be expected that a stronger and more aggressive cleanser might help remove pathogens from the skin, in fact a balance with skin mildness must be struck so as not to dry out the skin or strip away skin lipids or healthy commensal microbiota. Surfactant type and level have been strongly linked to pathogen inactivation efficacy of soaps (Shafa & Salton, 1960;Al-Adham, Haddadin & Collier, 2013;Jensen, Rogers & Schaffner, 2017;Simon et al, 2021). Anionic surfactants, are known to be effective against bacteria, and this is enhanced at higher surfactant levels.…”
Section: Surfactantsmentioning
confidence: 99%
See 1 more Smart Citation
“…For enveloped viruses, a major point of attraction to surfactant molecules is the lipid bilayer in which hydrophobic interaction may become the main driving force. In addition to hydrophobic interactions, electrostatics may also play a role, especially if the surfactant was oppositely charged [65]. Some surfactants might be bound within the lipid bilayer and this binding will raise the chemical potential of the surfactant in the bilayer, leading to thermodynamic instability [67].…”
Section: Suppression Experimentsmentioning
confidence: 99%
“…Carrouel et al (2021) suggested that some ingredients of mouthwashes reduce the activity of the virus [9]. Povidone-iodine and surfactants, including those found in toothpastes and mouthwashes, are known to inactivate enveloped viruses, including SARS-CoV-2 [9,10]. To further enhance the inhibitory effect of these ingredients on the entry of SARS-CoV-2 into host cells, it is also important to consider its effect on the virus' infection mechanism on the host cell side.…”
Section: Introductionmentioning
confidence: 99%